Amperometric Ascorbic Acid Biosensors Based on the Oxygen and Glassy Carbon Electrodes Modified with Ascorbate Oxidase Immobilized-silk Fibroin/polyethylene Glycol Membrane - Pacharawan Ratanasongtham (Science Faculty of Chiang Mai University, 2019)
Amperometric biosensors for the specific determination of ascorbic acid (AA) were developed by immobilizing ascorbate oxidase (ASOD) on a polyethylene glycol (PEG) modified silk fibroin (SF) membrane coupled to either the O2 electrode or the glassy carbon electrode (GCE). Both the O2 electrode and the GCE modified with SF/PEG/ASOD displayed their best sensor response at the same optimum conditions (0.40 mg/L of ASOD in phosphate buffer, pH 5). By comparing the responses of both AA biosensors, the GCE based biosensor showed better linearity (r2 = 0.999 in the range of 0.5-12.0 mM) with shorter response time (26 s) compared to the O2 electrode based biosensor (r2 = 0.997 in the range of 0.5-5.0 mM, response time 48 s). In addition, the GCE based biosensor exhibited better selectivity and had simpler preparation steps. However, both biosensors provided approximately the same sensitivity, but the O2 electrode based biosensor had a longer storage time (0.703 mA.mM-1, 9 days) than the GCE based one (0.695 mA.mM-1, 5 days). For both biosensors, there is little interference from citric acid, sodium chloride or ethanol, but some interference (2-4% error) from glucose.